As You Like It - Shakespeare, William (London Penguin Books, 1994)
Arden Performance Editions are ideal for anyone engaging with a Shakespeare play in performance. With clear facing-page notes giving definitions of words, easily accessible information about key textual variants, lineation, metrical ambiguities and pronunciation, each edition has been developed to open the play's possibilities and meanings to actors and students